Rare bird documentation form for Northern Goshawk at Green Valley State Park, 1980 - Stone, Tom, Jr.et al (1980)
Rare bird documentation form for a Northern Goshawk at Green Valley State Park in Union County, IA on April 4, 1980. Epson - sheet feed/flatbed